Determination of Trace Elements of Mimosa pudica from Different Parts by Microwave Digestion-Atomic Absorption Spectroscopy - YUAN, KE; LIN, YIN (Asian Journal of Chemistry, 2010)
The stem, leaf and flower of Mimosa pudica were digested with HNO3:HClO4 (4:1) and the contents of thirteen trace elements such as Zn, Fe, Cu, Mn, K, Ca, Mg, Ni, Cd, Pb, Cr, Co, Al, Se and As from different parts were determined by atomic absorption spectrophotometry. The relative standard deviation of the method is between 1.21 and 3.05 % and the recovery ratio by standard addition is between 97.2 and 103.1 %. The experimental result shows that the content of K, Mg, Ca, Fe and Mn which are beneficial to the human body in Mimosa pudica is high. The order from high to low of the additive weight (μg g-1) for the five kinds of elements in different parts is as follows: leaf > flower > stem. The content of the heavy metal trace elements Cr, Cd, Pb and As which are harmful to the human body in Mimosa pudica is lower, but the content of copper was high. The results provided scientific data for the further discussion of the relationship between the content of trace elements in Mimosa pudica and their relativity of medicine efficacy and development and the application of the resource.